Development of History Learning E-Module to Support Differentiated Learning - Eka Rimatuzzahriah; Ibrahim, Nurzengky; Abrar, Abrar (Lembaran Ilmu Kependidikan, 2024)
His study examines the development of a history learning E-Module that supports a differentiated learning approach at SMAN 86 Jakarta. In recent years, there has been a growing interest in incorporating technology into education, particularly in developing innovative learning materials that cater to diverse student needs.. This study examines the development of a history learning E-Module that supports a differentiated learning approach at SMAN 86 Jakarta. The main objective is to create an effective E-Module for history subjects using Moodle and analyze the module's feasibility and effectiveness. The expected benefits include increasing the effectiveness of learning for students and teachers, as well as inspiration for schools in developing digital teaching materials. The methodology used is Research and Development (R&D) with the Hannafin and Peck learning model, which involves needs analysis, design, development, and implementation. The study results show that E-Modules increase learning motivation and achievement, with interactive features that enrich the learning experience and technology allowing personalized learning. We recommend that teachers integrate personalization features further and that schools provide more technology training. We also recommend evaluating the long-term impact of E-Modules on differentiated education.